Perubahan Pekerjaan Beton Lining in Situ ke Beton Precast pada Jaringan Irigasi D.I. Tapin Kabupaten Tapin - Hafiz Darmawan (Lambung Mangkurat University Press, 2022)
This study aims to evaluate and analyze the method changes in the concrete lining of irrigation canals between in situ concrete and precast concrete. By evaluating the change in the work method, it was finally found that the method using Precast concrete has several advantages over in situ concrete. In terms of implementation, the quality of the concrete is increased, becoming K-225 (± 19 MPa) while the requirement is only K-175 (± 15 MPa). Besides that, Precast concrete can minimize material losses in construction time because it is cast on a precision plane, and the execution time can be significantly faster. As for the cost analysis, using Precast concrete, the price increased due to the increase in the quality of concrete, sash, and the addition of dowel bars. However, the analysis also shows that the more volume of Precast concrete, the lower the construction cost.